Bridging the Innovation Gap : Blueprint for the Innovative Enterprise - Huber, Daniel; Kaufmann, Heiner; Steinmann, Martin (Springer International Publishing : Imprint : Springer, 2017)
This book offers fresh insights into innovation management and its prerequisites. Based on these insights, the authors present a new and proven innovation system, which is being used in practice and has the potential to significantly increase the ability of enterprises to innovate. Starting with the innovation dilemma that enterprises face, the book analyses the concept of innovation as it is (mis)understood in practice, and identifies the missing element in current innovation theories - the innovation gap. Further, it asks whether today's enterprises are well suited for innovation and then describes a solution to the problems identified. The book also introduces a new and important element of the revised innovation process called "Exploration". From leadership issues to building a strong innovation model, it offers state-of-the-art knowledge, which can significantly boost the chances of innovation succeeding in enterprises.
Keywords: Technological innovations -- Management.; Technological innovations.; Industrial management.; Business.; Leadership.; Knowledge management.; Management.; elektronické knihy; electronic books